Sustainability Report dan Manajemen Laba Dengan Good Corporate Governance Quality Sebagai Pemoderasi - Kepakisan, I Gusti Agung Ayu Prabaningrat Dwi; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 32 No 2 (2022)DO - 10.24843/EJA.2022.v32.i02.p17, 2022)
The purpose of the study was to obtain empirical evidence regarding the effect of sustainability reports on earnings management and the effect of sustainability reports on earnings management with Good Corporate Governance Quality as moderating. The research was conducted at the Indonesia Stock Exchange, the data used is quantitative data. The data source of this research is using secondary data, the sample of this research is 10 companies with 5 years of research observation using purposive sampling method. The data were analyzed using moderate regression. The results of the study show that the sustainability report has a negative effect on earnings management and Good Corporate Governance Quality strengthens the negative effect of the sustainability report on earnings management. This is based on the Legitimacy and Agency theory, where the occurrence of earnings management can be influenced by Good Corporate Governance Quality. The higher the level of Good Corporate Governance Quality achieved by the company, it can suppress the occurrence of earnings management. Therefore ,  the higher the level of Good Corporate Governance Quality of a company, the greater the disclosure of the sustainability report by the company. Keywords: Profit; Profit Management; Sustainability Report; Quality of Good Corporate Governance.